Corporate governance in Kenya's public universities. (19th August 2014) - Mulili, Benjamin Mwanzia; Blessinger, Patrick
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose This research sought to explore the corporate governance practices adopted by public universities in Kenya, itself a developing country. Corporate governance practices in Africa, especially the sub-Saharan part, are weak and limited research has been done in this area. Design/methodology/approach The researcher adopted the realism paradigm and relied on qualitative data obtained from five case study organizations. A total of 15 informants were interviewed. The data was recorded, transcribed, and subjected to content analysis using the NVIVO software. Findings The researcher established that the governance of the said institutions is constrained by numerous challenges that include, among many others, large student numbers, overstretched facilities, insufficient government support, inadequate induction of new staff, resistance to change and cultures that support impunity on the part of some non-performing employees. Practical implications This research recommends several strategies that can be used to improve the governance of the said institutions and, by extension, that of similar institutions in developing countries. Originality/value The study provides empirical evidence to support the proposition that different corporate governance theories, such as the stakeholders theory, political theory and resource dependency theory, can be used simultaneously by the same firm. On this basis, the research suggests the adoption of a combined theory of corporate governance.